Healthcare professionals' perspectives of barriers to cancer care delivery for American Indian, rural, and frontier populations - Brandon M. Varilek; Sarah Mollman (Elsevier, 2024)
Objective: This descriptive qualitative study sought to understand the barriers affecting cancer care delivery from the perspective of healthcare professionals (HCPs) serving American Indian (AI), rural, and frontier populations. Methods: One-on-one, semi-structured interviews with multidisciplinary HCPs (N = 18) who provide cancer care to AI, rural, and frontier populations were conducted between January and April 2022. Interviews were conducted via Zoom. Data were analyzed following thematic content analysis methodologies. Results: Thematic content analysis revealed three major themes: (a) Access, (b) Time, and (c) Isolation. The themes represent the HCP perspectives of the needs and barriers of persons with cancer to whom they provide cancer care. Furthermore, these themes also reflect the barriers HCPs experience while providing cancer care to AI, rural and frontier populations. Conclusions: This study provides preliminary evidence for the need and strong multidisciplinary support for an early palliative care intervention in rural and frontier South Dakota (SD). This intervention could support the needs of persons with advanced cancer as well as the HCPs delivering cancer care in rural settings. Innovation: This study is the initial step to develop the first culturally responsive, nurse-led, early palliative care intervention for AI, rural, and frontier persons with advanced cancer in SD.